Copper alloys, copper alloy plastic processing materials, electronic and electrical equipment parts, terminals, bus bars, lead frames, heat dissipation substrates

A copper alloy with controlled composition and structure addresses conductivity, stress relaxation, and bending workability challenges, achieving high performance in high-temperature environments.

JP7604935B2Active Publication Date: 2024-12-24MITSUBISHI MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021022768
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-16
Publication Date
2024-12-24
Estimated Expiration
2041-02-16

AI Technical Summary

Technical Problem

Conventional copper materials used in electronic and electrical equipment parts face challenges with high electrical conductivity, stress relaxation resistance, and bending workability, especially in high-temperature environments, limiting their performance and size reduction.

Method used

A copper alloy with controlled composition and structure, including specific ranges of Mg, S, P, Se, Te, Sb, Bi, and As contents, along with Ag segregation at grain boundaries, achieves balanced electrical conductivity and stress relaxation resistance, enhanced by a crystal grain size and aspect ratio control.

Benefits of technology

The copper alloy exhibits high electrical conductivity (97% IACS or more), excellent stress relaxation resistance (10% residual stress rate at 150°C for 1000 hours), and improved bending workability, suitable for high-current and high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604935000007
    Figure 0007604935000007
  • Figure 0007604935000008
    Figure 0007604935000008
  • Figure 0007604935000001
    Figure 0007604935000001
Patent Text Reader

Abstract

To provide a copper alloy that is excellent in conductivity, stress relaxation resistance, and bendability.SOLUTION: A copper alloy contains Mg of more than 10 massppm to less than 100 massppm, with the balance being Cu and unavoidable impurities. The unavoidable impurities include S of 10 massppm or less, P of 10 massppm or less, Se of 5 massppm or less, Te of 5 massppm or less, Sb of 5 massppm or less, Bi of 5 massppm or less, and As of 5 massppm or less, with the total content of S, P, Se, Te, Sb, Bi and As being 30 massppm or less, the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] being 0.6 or more and 50 or less. The copper alloy has a conductivity of 97%IACS or more and a residual stress rate of 10% or more under the conditions of 150°C and 1000 hours, the average particle size of the crystal grains is 1 μm or more and 100 μm or less, and the crystal grains having an aspect ratio b / a of 0.3 or less constitutes 90% or less of the total number of the crystal grains, the aspect ratio b / a represented by the major axis a and the minor axis b.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copper alloy suitable for electronic and electric device parts such as terminals, bus bars, lead frames, and heat dissipation substrates, and to a copper alloy plastically processed material made of this copper alloy, electronic and electric device parts, terminals, bus bars, lead frames, and heat dissipation substrates. [Background technology]

[0002] Conventionally, highly conductive copper or copper alloys have been used for electronic and electric device components such as terminals, bus bars, lead frames, and heat dissipation substrates. Here, with the increase in current in electronic devices, electric devices, etc., the electronic and electric device parts used in these electronic devices, electric devices, etc. are being made larger and thicker in order to reduce current density and dissipate heat caused by Joule heating. In addition, with the increase in thickness of copper material, there is concern that the size of electric and electronic parts will increase if conventional processing methods are used.

[0003] In order to handle large currents, pure copper materials with excellent electrical conductivity, such as oxygen-free copper, are used in the above-mentioned electronic and electrical device components. However, pure copper materials have poor stress relaxation resistance, which indicates the degree to which a spring will sag due to heat, and there is a problem that they cannot be used stably in high-temperature environments. Therefore, Patent Document 1 discloses a copper rolled sheet containing Mg in the range of 0.005 mass % or more and less than 0.1 mass %.

[0004] The copper rolled sheet described in Patent Document 1 contains Mg in the range of 0.005 mass% or more and less than 0.1 mass%, with the remainder being Cu and unavoidable impurities. By dissolving Mg in the copper matrix, it is possible to improve the strength and stress relaxation resistance without significantly decreasing the electrical conductivity. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-056414 A Summary of the Invention [Problem to be solved by the invention]

[0006] Recently, there has been a demand for further improving the electrical conductivity of the copper materials constituting the above-mentioned electronic and electrical device components in order to sufficiently suppress heat generation when a large current is passed through them and so that they can be used in applications in which pure copper materials were previously used. Furthermore, in order to reduce the size of electrical and electronic components, there was a need to develop materials that could be processed into more complex bends.

[0007] Furthermore, the above-mentioned electronic and electric device parts are often used in high-temperature environments such as engine compartments, and therefore the copper materials constituting the electronic and electric device parts need to have improved stress relaxation resistance more than ever before. In other words, there is a demand for copper materials with a good balance between improved electrical conductivity and stress relaxation resistance.

[0008] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a copper alloy, a copper alloy plastically worked material, an electronic / electronic device part, a terminal, a bus bar, a lead frame, and a heat dissipation board which have high electrical conductivity and excellent stress relaxation resistance properties as well as excellent bending workability. [Means for solving the problem]

[0009] In order to solve this problem, the inventors conducted extensive research and discovered that in order to achieve a good balance between high electrical conductivity and excellent stress relaxation resistance, it is possible to improve electrical conductivity and stress relaxation resistance to a higher level than ever before by adding a trace amount of Mg, regulating the contents of elements that form compounds with Mg, and further controlling the structure in accordance with the composition. Furthermore, the inventors discovered that it is possible to improve bending workability by appropriately controlling the structure.

[0010] The present invention has been made based on the above-mentioned findings, and the copper alloy of the present invention has a composition in which the Mg content is in the range of more than 10 massppm and less than 100 massppm, with the balance being Cu and unavoidable impurities, and among the unavoidable impurities, the S content is 10 massppm or less, the P content is 10 massppm or less, the Se content is 5 massppm or less, the Te content is 5 massppm or less, the Sb content is 5 massppm or less, the Bi content is 5 massppm or less, and the As content is 5 massppm or less, and The total content of P, Se, Te, Sb, Bi and As is 30 mass pm or less, the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As], where the Mg content is [Mg] and the total content of S, P, Se, Te, Sb, Bi and As is [S+P+Se+Te+Sb+Bi+As], is within the range of 0.6 to 50, the electrical conductivity is 97% IACS or more, the residual stress rate is 10% or more at 150°C and 1000 hours, the average grain size is within the range of 1 μm to 100 μm, For the plane perpendicular to the rolling direction (TD plane), an EBSD measurement device (FEI Quanta FEG 450, EDAX / TSL (now AMETEK) OIM Data Collection) and analysis software (EDAX / TSL (now AMETEK) OIM Data Analysis Ver. 7.3.1) were used to measure the electron beam acceleration voltage of 20 kV, with measurement intervals of 100,000 μm at 0.11 μm steps. 2 In the above area, the misorientation of each crystal grain (including twins) is analyzed, excluding measurement points with a CI value of 0.1 or less. Measurement points where the misorientation between adjacent measurement points is 15° or more are considered to be grain boundaries, and the minimum grain size on the EBSD is set to 2 pixels, and the grain size of each crystal grain is calculated. The aspect ratio b / a, which is expressed by the major axis a and the minor axis b, is 0.3 or less, and the proportion of crystal grains in the number of crystal grains is 90% or less.

[0011] In the copper alloy having this configuration, the contents of Mg and the elements S, P, Se, Te, Sb, Bi, and As which form compounds with Mg are specified as described above, and the crystal structure is specified as described above. Therefore, the trace amount of Mg added dissolves in the copper matrix, thereby improving the stress relaxation resistance without significantly decreasing the electrical conductivity. Specifically, the electrical conductivity can be made 97% IACS or more, and the residual stress rate can be made 10% or more at 150°C for 1000 hours, making it possible to achieve both high electrical conductivity and excellent stress relaxation resistance. In addition, the average grain size is within the range of 1 μm or more and 100 μm or less, and the proportion of crystal grains having an aspect ratio b / a, expressed by the major axis a and the minor axis b, of 0.3 or less is 90% or less, so that the material has excellent bending workability.

[0012] In the copper alloy of the present invention, the Ag content is preferably within the range of 5 massppm to 20 massppm. In this case, since the Ag content is within the above range, Ag segregates near the grain boundaries, grain boundary diffusion is suppressed, and the stress relaxation resistance can be further improved.

[0013] In the copper alloy of the present invention, the half-softening temperature is preferably 200° C. or higher. In this case, since the semi-softening temperature is set to 200° C. or higher, the heat resistance is sufficiently excellent and the material can be used stably even in a high-temperature environment.

[0014] The plastically worked copper alloy material of the present invention is characterized by being made of the above-mentioned copper alloy. Since the copper alloy plastically processed material having this configuration is made of the above-mentioned copper alloy, it has excellent electrical conductivity, stress relaxation resistance, and bending workability, and is particularly suitable as a material for electronic and electrical device components such as terminals, bus bars, lead frames, and heat dissipation substrates used in large current applications and high temperature environments.

[0015] Here, the plastically worked copper alloy material of the present invention may be a rolled plate having a thickness within the range of 0.1 mm to 10 mm. In this case, since the thickness of the rolled plate is within the range of 0.1 mm to 10 mm, this copper alloy plastically processed material (rolled plate) can be punched or bent to form electronic / electrical device parts such as terminals, bus bars, lead frames, and heat dissipation boards.

[0016] In addition, the plastically worked copper alloy material of the present invention preferably has a metal plating layer on the surface. In this case, since it has a metal plating layer on the surface, it is particularly suitable as a material for electronic and electric device parts such as terminals, bus bars, lead frames, and heat dissipation substrates. Examples of the metal plating layer include Sn plating, Ag plating, Ni plating, Au plating, Pd plating, Rh plating, etc. In the present invention, "Sn plating" includes pure Sn plating or Sn alloy plating, "Ag plating" includes pure Ag plating or Ag alloy plating, "Ni plating" includes pure Ni plating or Ni alloy plating, "Au plating" includes pure Au plating or Au alloy plating, "Pd plating" includes pure Pd plating or Pd alloy plating, and "Rh plating" includes pure Rh plating or Rh alloy plating.

[0017] The electronic / electrical device part of the present invention is characterized in that it is made of the above-mentioned copper alloy plastically processed material. The electronic / electrical device part in the present invention includes terminals, bus bars, lead frames, heat dissipation substrates, etc. Since the electronic / electrical device parts having this configuration are manufactured using the above-mentioned copper alloy plastically processed material, they can exhibit excellent characteristics even in large current applications and high temperature environments.

[0018] The terminal of the present invention is characterized by being made of the above-mentioned plastically worked copper alloy material. The terminal having this configuration is manufactured using the above-mentioned copper alloy plastically processed material, and therefore can exhibit excellent characteristics even in large current applications and high temperature environments.

[0019] The bus bar of the present invention is characterized by being made of the above-mentioned plastically worked copper alloy material. The busbar having this configuration is manufactured using the above-mentioned copper alloy plastically processed material, and therefore can exhibit excellent characteristics even in high current applications and high temperature environments.

[0020] The lead frame of the present invention is characterized in that it is made of the above-mentioned plastically worked copper alloy material. The lead frame having this configuration is manufactured using the above-mentioned copper alloy plastically processed material, and therefore can exhibit excellent characteristics even in high current applications and high temperature environments.

[0021] The heat dissipation board of the present invention is characterized in that it is made of the above-mentioned copper alloy. The heat dissipation board of this configuration is made of the above-mentioned copper alloy, and therefore can exhibit excellent characteristics even in a high-temperature environment. Effect of the Invention

[0022] According to the present invention, it is possible to provide a copper alloy, a copper alloy plastically worked material, an electronic / electronic device part, a terminal, a bus bar, a lead frame, and a heat dissipation substrate, which have high electrical conductivity and excellent stress relaxation resistance properties as well as excellent bending workability. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a flow diagram of a method for producing a copper alloy according to an embodiment of the present invention. [Diagram 2] 1 is a photograph showing the results of EBSD observation of Example 14 of the present invention in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, a copper alloy according to one embodiment of the present invention will be described. The copper alloy of this embodiment has a composition in which the Mg content is in the range of more than 10 massppm and less than 100 massppm, with the balance being Cu and unavoidable impurities. Of the unavoidable impurities, the S content is 10 massppm or less, the P content is 10 massppm or less, the Se content is 5 massppm or less, the Te content is 5 massppm or less, the Sb content is 5 massppm or less, the Bi content is 5 massppm or less, and the As content is 5 massppm or less, and the total content of S, P, Se, Te, Sb, Bi, and As is 30 massppm or less.

[0025] If the content of Mg is defined as [Mg] and the total content of S, P, Se, Te, Sb, Bi and As is defined as [S+P+Se+Te+Sb+Bi+As], the mass ratio thereof, [Mg] / [S+P+Se+Te+Sb+Bi+As], is within the range of 0.6 or more and 50 or less. In the copper alloy of this embodiment, the Ag content may be within a range of 5 massppm or more and 20 massppm or less.

[0026] Moreover, in the copper alloy of this embodiment, the electrical conductivity is set to 97% IACS or more, and the residual stress rate is set to 10% or more at 150° C. for 1000 hours. In the copper alloy of this embodiment, the half-softening temperature is preferably 200° C. or higher.

[0027] Furthermore, in the copper alloy of this embodiment, the average grain size of the crystal grains is set within the range of 1 μm to 100 μm. In addition, the percentage of crystal grains having an aspect ratio b / a, expressed by the major axis a and the minor axis b, of 0.3 or less is set to 90% or less.

[0028] Here, the reasons for specifying the component composition, various characteristics, and crystal structure of the copper alloy of this embodiment as described above will be explained below.

[0029] (Mg) Mg is an element that has the effect of improving stress relaxation resistance without significantly decreasing electrical conductivity by dissolving in the copper matrix. In addition, dissolving Mg in the copper matrix increases the half-softening temperature and improves heat resistance. Here, if the Mg content is 10 massppm or less, the effect of the Mg may not be fully exhibited, whereas if the Mg content is 100 massppm or more, the electrical conductivity may decrease. For the above reasons, in this embodiment, the Mg content is set within the range of more than 10 massppm and less than 100 massppm.

[0030] In order to further improve the stress relaxation resistance, the lower limit of the Mg content is preferably 20 massppm or more, more preferably 30 massppm or more, and even more preferably 40 massppm or more. In order to further increase the electrical conductivity, the upper limit of the Mg content is preferably less than 90 massppm, more preferably less than 80 massppm, and even more preferably less than 70 massppm.

[0031] (S, P, Se, Te, Sb, Bi, As) The above-mentioned elements S, P, Se, Te, Sb, Bi, and As are generally elements that tend to be mixed into copper alloys. These elements tend to react with Mg to form compounds, which may reduce the solid solution effect of the trace amount of Mg added. For this reason, the content of these elements must be strictly controlled. Therefore, in this embodiment, the S content is limited to 10 massppm or less, the P content is limited to 10 massppm or less, the Se content is limited to 5 massppm or less, the Te content is limited to 5 massppm or less, the Sb content is limited to 5 massppm or less, the Bi content is limited to 5 massppm or less, and the As content is limited to 5 massppm or less. Furthermore, the total content of S, P, Se, Te, Sb, Bi, and As is limited to 30 mass ppm or less.

[0032] The S content is preferably 9 massppm or less, and more preferably 8 massppm or less. The P content is preferably 6 massppm or less, and more preferably 3 massppm or less. The Se content is preferably 4 massppm or less, and more preferably 2 massppm or less. The content of Te is preferably 4 massppm or less, and more preferably 2 massppm or less. The Sb content is preferably 4 massppm or less, and more preferably 2 massppm or less. The Bi content is preferably 4 massppm or less, and more preferably 2 massppm or less. The As content is preferably 4 massppm or less, and more preferably 2 massppm or less. Furthermore, the total content of S, P, Se, Te, Sb, Bi and As is preferably 24 massppm or less, and more preferably 18 massppm or less.

[0033] ([Mg] / [S+P+Se+Te+Sb+Bi+As]) As described above, elements such as S, P, Se, Te, Sb, Bi, and As tend to react with Mg to form compounds, and therefore in this embodiment, the form of Mg is controlled by defining the ratio of the Mg content to the total content of S, P, Se, Te, Sb, Bi, and As. If the content of Mg is [Mg] and the total content of S, P, Se, Te, Sb, Bi and As is [S+P+Se+Te+Sb+Bi+As], when the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] exceeds 50, Mg is present in the copper in an excessive solid solution state, which may reduce electrical conductivity. On the other hand, when the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] is less than 0.6, Mg is not sufficiently dissolved, which may result in insufficient improvement in stress relaxation resistance. Therefore, in this embodiment, the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] is set within the range of 0.6 to 50.

[0034] In order to further increase the electrical conductivity, the upper limit of the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] is preferably set to 35 or less, and more preferably set to 25 or less. In order to further improve the stress relaxation resistance, the lower limit of the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] is preferably set to 0.8 or more, and more preferably set to 1.0 or more.

[0035] (Ag: 5 massppm or more and 20 massppm or less) Ag is hardly able to dissolve in the Cu matrix at temperatures below 250°C, the range in which electronic and electrical equipment is typically used. For this reason, trace amounts of Ag added to copper segregate near grain boundaries. This prevents atoms from moving at the grain boundaries and suppresses grain boundary diffusion, further improving heat resistance and stress relaxation resistance. When the Ag content is 5 massppm or more, the effect of the Ag can be sufficiently exhibited, whereas when the Ag content is 20 massppm or less, the increase in the manufacturing cost can be suppressed. For the above reasons, in the present embodiment, when Ag is added, the Ag content is set to a range of 5 massppm to 20 massppm. In addition, when Ag is not intentionally added, the Ag content is not particularly limited.

[0036] In order to further improve the heat resistance and stress relaxation resistance, the lower limit of the Ag content is preferably 6 massppm or more, more preferably 7 massppm or more, and even more preferably 8 massppm or more. In order to reliably suppress an increase in cost, the upper limit of the Ag content is preferably 18 massppm or less, more preferably 16 massppm or less, and even more preferably 14 massppm or less. Ag may be contained as an inevitable impurity or may be intentionally added. When Ag is not intentionally contained but is contained as an impurity, when Ag is not intentionally added, the Ag content is not particularly limited.

[0037] (Other unavoidable impurities) Other inevitable impurities besides the above-mentioned elements include Al, B, Ba, Be, Ca, Cd, Cr, Sc, rare earth elements, V, Nb, Ta, Mo, Ni, W, Mn, Re, Ru, Sr, Ti, Os, Co, Rh, Ir, Pb, Pd, Pt, Au, Zn, Zr, Hf, Hg, Ga, In, Ge, Y, Tl, N, Si, Sn, Li, etc. These inevitable impurities may be contained to the extent that they do not affect the characteristics. Here, since these unavoidable impurities may reduce electrical conductivity, the total amount is preferably 0.1 mass% or less, more preferably 0.05 mass% or less, even more preferably 0.03 mass% or less, and further preferably 0.01 mass% or less. Moreover, the upper limit of the content of each of these unavoidable impurities is preferably 10 massppm or less, more preferably 5 massppm or less, and even more preferably 2 massppm or less.

[0038] (Conductivity: 97%IACS or higher) The copper alloy of this embodiment has an electrical conductivity of 97% IACS or more. By making the electrical conductivity 97% IACS or more, heat generation during electrical current flow is suppressed, and the copper alloy can be favorably used as a substitute for pure copper material in electronic and electrical device parts such as terminals, bus bars, lead frames, and heat dissipation substrates. The electrical conductivity is preferably 97.5% IACS or more, more preferably 98.0% IACS or more, even more preferably 98.5% IACS or more, and even more preferably 99.0% IACS or more.

[0039] (Residual stress rate (150℃, 1000 hours): 10% or more) In the copper alloy of this embodiment, the residual stress rate is 10% or more at 150°C for 1000 hours. If the residual stress rate under this condition is high, permanent deformation can be suppressed even when used in a high-temperature environment, and a decrease in contact pressure can be suppressed. Therefore, the copper rolled sheet of this embodiment can be used as a terminal or the like used in a high-temperature environment such as around the engine room of an automobile. The residual stress rate is preferably 20% or more, more preferably 30% or more, even more preferably 40% or more, and even more preferably 50% or more at 150°C for 1000 hours.

[0040] (Semi-softening temperature: 200℃ or higher) In the copper alloy of this embodiment, when the semi-softening temperature is high, the softening phenomenon due to recovery and recrystallization of the copper material is unlikely to occur even at high temperatures, making it possible to apply the alloy to current-carrying members used in high-temperature environments. For this reason, in this embodiment, it is preferable that the semi-softening temperature in the 1-hour heat treatment is equal to or higher than 200° C. In this embodiment, the semi-softening temperature was evaluated by measuring the Vickers hardness. The semi-softening temperature in one hour of heat treatment is more preferably 225° C. or higher, even more preferably 250° C. or higher, and even more preferably 275° C. or higher.

[0041] (Average grain size) In the copper alloy having the above composition, when the average grain size of the crystal grains is fine, the proof stress and bending workability are improved, but the stress relaxation resistance tends to decrease. On the other hand, when the average grain size of the crystal grains is coarse, the stress relaxation resistance is improved, but the proof stress and bending workability tend to decrease. For this reason, in the copper alloy of this embodiment, in order to achieve a good balance between yield strength, bending workability, and stress relaxation resistance, the average grain size of the crystal grains is set within the range of 1 μm to 100 μm. In order to sufficiently improve the stress relaxation resistance, the lower limit of the average grain size is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. On the other hand, in order to sufficiently improve the yield strength and bending workability, the upper limit of the average grain size is preferably 90 μm or less, more preferably 80 μm or less, and even more preferably 70 μm or less.

[0042] (Proportion of crystal grains with aspect ratio b / a of 0.3 or less) The aspect ratio b / a, which is expressed by the long axis a and short axis b of a crystal grain (including twin crystals), is an index of the degree of processing of a material, and the higher the proportion of crystal grains with a small aspect ratio b / a, the higher the degree of processing. This results in a higher proportion of crystals with high processing strain, which tends to reduce bending workability. Therefore, in this embodiment, the proportion of crystal grains with an aspect ratio b / a of 0.3 or less is controlled to 90% or less, thereby improving bending workability while maintaining the yield strength. The proportion of crystal grains having an aspect ratio b / a of 0.3 or less is preferably 85% or less, and more preferably 80% or less.

[0043] Next, the method for producing the copper alloy according to this embodiment having the above-described configuration will be described with reference to the flow diagram shown in FIG.

[0044] (Melting and casting process S01) First, the copper raw material is melted, and the above-mentioned elements are added to the molten copper to adjust the composition, thereby producing a molten copper alloy. The various elements can be added in the form of simple elements or master alloys. Raw materials containing the above-mentioned elements may be melted together with the copper raw material. Recycled materials and scrap materials of the present alloy may also be used. Here, the copper raw material is preferably so-called 4NCu having a purity of 99.99 mass% or more, or so-called 5NCu having a purity of 99.999 mass% or more. During melting, in order to suppress oxidation of Mg and to reduce the hydrogen concentration, it is preferable to perform atmospheric melting in an inert gas atmosphere (e.g., Ar gas) with a low vapor pressure of H2O, and to keep the holding time during melting to a minimum. The molten copper alloy having the adjusted composition is then poured into a mold to produce an ingot. When mass production is taken into consideration, it is preferable to use a continuous casting method or a semi-continuous casting method.

[0045] (Homogenization / solution process S02) Next, a heat treatment is performed to homogenize and dissolve the obtained ingot. In the ingot, intermetallic compounds mainly composed of Cu and Mg may be present, which are generated by the segregation and concentration of Mg during the solidification process. In order to eliminate or reduce these segregations and intermetallic compounds, the ingot is heated to 300°C or higher and 1080°C or lower, thereby homogenizing Mg in the ingot and dissolving Mg in the parent phase. The homogenization / solution process S02 is preferably performed in a non-oxidizing or reducing atmosphere.

[0046] Here, if the heating temperature is less than 300°C, the solution treatment will be incomplete, and there is a risk that a large amount of intermetallic compounds mainly composed of Cu and Mg will remain in the parent phase. On the other hand, if the heating temperature exceeds 1080°C, part of the copper material will become liquid, and there is a risk that the structure and surface condition will become non-uniform. Therefore, the heating temperature is set in the range of 300°C to 1080°C. In order to improve the efficiency of the rough processing and to homogenize the structure, hot working may be performed after the homogenization / solution treatment step S02. In this case, the processing method is not particularly limited, and for example, rolling, drawing, extrusion, groove rolling, forging, pressing, etc. can be used. In addition, the hot working temperature is preferably within the range of 300°C to 1080°C.

[0047] (Rough machining process S03) In order to process the steel into a desired shape, rough processing is performed. The temperature conditions in the rough processing step S03 are not particularly limited, but in order to suppress recrystallization or to improve dimensional accuracy, it is preferable to perform cold or warm rolling within the range of -200°C to 200°C, and room temperature is particularly preferable. The processing rate is preferably 20% or more, and more preferably 30% or more. The processing method is not particularly limited, and for example, rolling, drawing, extrusion, groove rolling, forging, pressing, etc. can be used.

[0048] (Intermediate heat treatment process S04) After the rough machining step S03, a heat treatment is carried out to soften the material to improve workability or to form a recrystallized structure. In the intermediate heat treatment step S04, it is preferable to appropriately set the heating temperature and heating time conditions in order to obtain an appropriate crystal grain size, and typically, the heating temperature is set to 200° C. or more and 900° C. or less, and the heating time is set to 1 second or more and 24 hours or less. However, since the crystal grain size has some effect on bending workability and stress relaxation resistance characteristics, it is preferable to measure the recrystallized grains by the intermediate heat treatment and appropriately select the heating temperature and heating time conditions. In addition, a short-time heat treatment in a continuous annealing furnace is preferable, and when Ag is added, localized segregation of Ag to grain boundaries can be prevented. In addition, in order to make the segregation of Ag to grain boundaries more uniform, the intermediate heat treatment step S04 and the upper processing step S05 described later may be repeatedly performed.

[0049] (Top front processing step S05) In order to process the copper material after the intermediate heat treatment step S04 into a predetermined shape, the upper pre-processing is performed. The temperature conditions in this upper pre-processing step S05 are not particularly limited, but it is preferable to set the temperature within the range of -200°C to 200°C, which is cold or warm processing, in order to suppress recrystallization or softening during processing, and room temperature is particularly preferable. The processing rate is appropriately selected so as to approximate the final shape, but it is preferable to set it to 5% or more in order to improve strength by work hardening. In addition, if rolling is selected, the rolling rate is preferably 90% or less in order to set the proof stress to 450 MPa or less in order to prevent curling when wound into a coil. Furthermore, if the working rate exceeds 90%, the proportion of crystal grains with an aspect ratio of 0.3 or less will not be 90% or less, and a worked structure will be formed, which may result in a decrease in bending workability. Therefore, it is preferable to set the working rate to 90% or less. The processing method is not particularly limited, and for example, rolling, drawing, extrusion, groove rolling, forging, pressing, etc. can be used.

[0050] (Mechanical surface treatment process S06) After the upper pre-processing step S05, a mechanical surface treatment is performed. The mechanical surface treatment is a treatment that applies a compressive stress to the surface vicinity after the desired shape is almost obtained, and has the effect of improving the stress relaxation resistance characteristic. For mechanical surface treatment, various commonly used methods can be used, such as shot peening, blasting, lapping, polishing, buffing, grinder polishing, sandpaper polishing, tension leveler treatment, and light rolling with a low reduction rate per pass (a reduction rate per pass of 1 to 10%, repeated three or more times). By applying this mechanical surface treatment to copper alloys containing Mg, the stress relaxation resistance is significantly improved.

[0051] (Finishing heat treatment process S07) Next, the plastically worked material obtained by the mechanical surface treatment step S06 may be subjected to a finish heat treatment in order to remove segregation of contained elements to grain boundaries and residual strain. The heat treatment temperature is preferably within a range of 100°C to 500°C. In this final heat treatment step S07, the heat treatment conditions must be set so as to avoid a significant decrease in strength due to recrystallization. For example, it is preferable to hold the steel at 450°C for about 0.1 to 10 seconds, and at 250°C for 1 minute to 100 hours. This heat treatment is preferably carried out in a non-oxidizing atmosphere or a reducing atmosphere. There are no particular limitations on the heat treatment method, but a short-time heat treatment using a continuous annealing furnace is preferable in terms of the effect of reducing production costs. Furthermore, the above-mentioned upper pre-processing step S05, the mechanical surface treatment step S06, and the finish heat treatment step S07 may be repeatedly performed.

[0052] In this manner, the copper alloy (plastically worked copper alloy material) according to this embodiment is produced. The plastically worked copper alloy material produced by rolling is called a rolled copper alloy sheet. Here, when the thickness of the plastically worked copper alloy material is 0.1 mm or more, it is suitable for use as a conductor in large current applications. Also, when the thickness of the plastically worked copper alloy material is 10.0 mm or less, the increase in the load of the press machine can be suppressed, productivity per unit time can be secured, and manufacturing costs can be reduced. For this reason, the sheet thickness of the plastically worked copper alloy material (rolled copper alloy material) is preferably within the range of 0.1 mm to 10.0 mm. The lower limit of the sheet thickness of the plastically worked copper alloy material (rolled copper alloy material) is preferably 0.5 mm or more, more preferably 1.0 mm or more, while the upper limit of the sheet thickness of the plastically worked copper alloy material (rolled copper alloy material) is preferably less than 9.0 mm, more preferably less than 8.0 mm. Moreover, a metal plating layer (for example, Sn plating, Ag plating, Ni plating, Au plating, Pd plating, Rh plating, etc.) may be formed on the surface of the plastically worked copper alloy material (rolled copper alloy material) of this embodiment.

[0053] In the copper alloy of the present embodiment having the above-mentioned configuration, the content of Mg is within the range of more than 10 massppm and less than 100 massppm, the content of S, which is an element that forms a compound with Mg, is 10 massppm or less, the content of P is 10 massppm or less, the content of Se is 5 massppm or less, the content of Te is 5 massppm or less, the content of Sb is 5 massppm or less, the content of Bi is 5 massppm or less, the content of As is 5 massppm or less, and the total content of S, P, Se, Te, Sb, Bi, and As is limited to 30 massppm or less, so that the trace amount of added Mg can be dissolved in the copper matrix, and the stress relaxation resistance can be improved without significantly decreasing the electrical conductivity.

[0054] Furthermore, when the content of Mg is [Mg] and the total content of S, P, Se, Te, Sb, Bi, and As is [S+P+Se+Te+Sb+Bi+As], the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] is set within the range of 0.6 or more and 50 or less, so it is possible to sufficiently improve the stress relaxation resistance without reducing the electrical conductivity due to excessive Mg solid solution. Furthermore, since the average grain size is within the range of 1 μm or more and 100 μm or less, it is possible to achieve a good balance between yield strength, bending workability, and stress relaxation resistance. Therefore, according to the copper alloy of this embodiment, the electrical conductivity can be made 97% IACS or more, and the residual stress rate can be made 10% or more at 150°C for 1000 hours, making it possible to achieve both high electrical conductivity and excellent stress relaxation resistance.

[0055] Furthermore, the average grain size is within the range of 1 μm or more and 100 μm or less, and the proportion of crystal grains having an aspect ratio b / a, expressed by the major axis a and the minor axis b, of 0.3 or less is 90% or less, so that the material has excellent bending workability.

[0056] Furthermore, in the copper alloy of this embodiment, when the content of Ag is within the range of 5 massppm or more and 20 massppm or less, Ag segregates near the grain boundaries, and the grain boundary diffusion is suppressed by this Ag, so that it is possible to further improve the stress relaxation resistance characteristic. Moreover, in the copper alloy of this embodiment, when the half-softening temperature is 200° C. or higher, the heat resistance is sufficiently excellent and the alloy can be stably used even in a high-temperature environment.

[0057] The copper alloy plastically worked material of this embodiment is made of the above-mentioned copper alloy, and therefore has excellent electrical conductivity, stress relaxation resistance, and bending workability, and is particularly suitable as a material for electronic and electric device parts such as terminals, bus bars, lead frames, and heat dissipation substrates. Furthermore, when the copper alloy plastically worked material of this embodiment is made into a rolled plate having a thickness in the range of 0.1 mm to 10 mm, the copper alloy plastically worked material (rolled plate) can be punched or bent to relatively easily form electronic / electrical device parts such as terminals, bus bars, lead frames, and heat dissipation boards. In addition, when a metal plating layer (e.g., Sn plating, Ag plating, Ni plating, Au plating, Pd plating, Rh plating, etc.) is formed on the surface of the copper alloy plastically worked material of this embodiment, it is particularly suitable as a material for electronic / electrical device parts such as terminals, bus bars, and heat dissipation substrates.

[0058] Furthermore, the electronic / electrical device components (terminals, bus bars, lead frames, heat dissipation substrates, etc.) of this embodiment are made of the above-mentioned copper alloy plastically processed material and copper alloy, and therefore can exhibit excellent characteristics even in large current applications and high temperature environments.

[0059] The copper alloy, the copper alloy plastically processed material, and the electronic / electrical device parts (terminals, bus bars, lead frames, etc.) according to the embodiments of the present invention have been described above. However, the present invention is not limited thereto, and appropriate modifications can be made without departing from the technical spirit of the invention. For example, in the above-described embodiment, an example of a manufacturing method for a copper alloy (copper alloy plastically processed material) has been described, but the manufacturing method for the copper alloy is not limited to that described in the embodiment, and the copper alloy may be manufactured by appropriately selecting an existing manufacturing method. EXAMPLES

[0060] The results of experiments carried out to confirm the effects of the present invention will be described below. A raw material consisting of pure copper with a purity of 99.999 mass% or more obtained by the zone melting refining method was placed in a high-purity graphite crucible and melted by high-frequency induction in an atmospheric furnace with an Ar gas atmosphere. To the obtained molten copper, 0.1 mass% of various master alloys made from high purity copper of 6N (purity of 99.9999 mass%) or more and pure metals having a purity of 2N (purity of 99 mass%) or more were added to adjust the composition, and the molten copper was poured into a mold made of insulating material (isowool) to produce ingots with the composition shown in Tables 1 and 2. The size of the ingot was about 30 mm thick x about 60 mm wide x about 150 to 200 mm long.

[0061] The obtained ingot was heated at 900°C for 1 hour in an Ar gas atmosphere to dissolve the Mg, the surface was ground to remove the oxide film, and then cut to a specified size. The thickness was then adjusted appropriately to the final thickness and cut. Each cut sample was roughly rolled (rough processing step) under the conditions shown in Tables 3 and 4, and then intermediate heat treatment was performed under the conditions shown in Tables 3 and 4.

[0062] Next, upper pre-rolling (upper pre-processing step) was carried out under the conditions shown in Tables 3 and 4. These samples were then subjected to a mechanical surface treatment process according to the methods described in Tables 3 and 4. The buffing was carried out using #1000 abrasive paper. The tension leveler is equipped with multiple φ16mm rolls, and the line tension is 300N / mm 2 The study was carried out at. Light rolling (rolling with a low reduction rate per pass) was performed with the final three passes having a reduction rate of 4% per pass. Thereafter, a final heat treatment was carried out under the conditions shown in Tables 3 and 4, and strip materials having the thickness and width of approximately 60 mm shown in Tables 3 and 4 were produced.

[0063] The obtained strips were evaluated for the following items.

[0064] (composition analysis) Measurement samples were taken from the resulting ingot, and Mg was measured using inductively coupled plasma optical emission spectrometry, and other elements were measured using a glow discharge mass spectrometer (GD-MS). The measurements were taken at two locations, the center and the end in the width direction, and the larger content was recorded as the content of the sample. As a result, it was confirmed that the component composition was as shown in Tables 1 and 2.

[0065] (conductivity) Test pieces measuring 10 mm wide and 60 mm long were taken from the strip material for property evaluation, and electrical resistance was measured by the four-terminal method. The dimensions of the test pieces were also measured using a micrometer, and the volume of the test pieces was calculated. The electrical conductivity was then calculated from the measured electrical resistance value and volume. The test pieces were taken so that their longitudinal direction was parallel to the rolling direction of the strip material for property evaluation. The evaluation results are shown in Tables 5 and 6.

[0066] (Stress relaxation resistance) The stress relaxation resistance test was carried out by applying stress using a method conforming to the cantilever beam screw method of the Japan Copper and Brass Association technical standard JCBA-T309:2004, and measuring the residual stress rate after holding at a temperature of 150°C for 1000 hours. The evaluation results are shown in Tables 5 and 6. The test method was to take test pieces (10 mm wide) from each strip material for property evaluation in a direction parallel to the rolling direction, set the initial deflection displacement to 2 mm, and adjust the span length so that the maximum surface stress of the test piece was 80% of the yield strength. The maximum surface stress is determined by the following formula. Maximum surface stress (MPa) = 1.5Etδ0 / L s 2 however, E: Young's modulus (MPa) t: sample thickness (mm) δ0: Initial deflection displacement (mm) L s : Span length (mm) It is. Residual stress rate was measured from bending tendency after holding at 150℃ for 1000 hours, and stress relaxation resistance was evaluated. The residual stress rate was calculated using the following formula. Residual stress rate (%)=(1-δ t / δ0)×100 however, δ t: Permanent deflection displacement after 1000 hours at 150℃ (mm) - Permanent deflection displacement after 24 hours at room temperature (mm) δ0: Initial deflection displacement (mm) It is.

[0067] (Average grain size) The surface perpendicular to the width direction of rolling, i.e. the TD (transverse direction) surface, was used as the observation surface, and mechanical polishing was performed using waterproof abrasive paper and diamond abrasive grains, followed by finish polishing using a colloidal silica solution. After polishing, etching was performed using a mixture of sulfuric acid and nitric acid as an etchant, and the metal structure was observed under an optical microscope. The grain size was measured according to the JIS H 0501 cutting method, where five lines of a given length were drawn vertically and horizontally, the number of grains that were completely cut was counted, and the average of the cut lengths was taken as the average grain size. The evaluation results are shown in Tables 5 and 6.

[0068] (Aspect Ratio) The surface perpendicular to the rolling direction of the strip material for property evaluation (TD surface) was mechanically polished using waterproof polishing paper and diamond abrasive grains, and then final polished using colloidal silica solution. Then, EBSD measurement equipment (FEI's Quanta FEG 450, EDAX / TSL's (currently AMETEK's) OIM Data Collection) and analysis software (EDAX / TSL's (currently AMETEK's) OIM Data Analysis Ver.7.3.1 ) was used to analyze the misorientation of each crystal grain (including twins) with an area of ​​100,000 μm2 or more, with an electron beam acceleration voltage of 20 kV and measurement intervals of 0.11 μm, excluding measurement points with a CI value of 0.1 or less, and the aspect ratio was measured by taking the major axis of each crystal grain as a and the minor axis as b, with measurement points between which the misorientation between adjacent measurement points was 15° or more as grain boundaries. In measuring the aspect ratio, the grain size on EBSD was measured with a grain tolerance angle of 5° and a minimum grain size of 2 pixels. The percentage of crystal grains with an aspect ratio b / a of 0.3 or less was then measured. The evaluation results are shown in Tables 5 and 6. The EBSD observation results for Example 14 of the present invention are shown in FIG.

[0069] (semi-softening temperature) The semi-softening temperature was evaluated by obtaining an isochronal softening curve based on Vickers hardness after one hour of heat treatment, with reference to JCBA T325:2013 of the Japan Copper and Brass Association, and determining the intermediate value between the hardness before heat treatment and the hardness when completely softened. The Vickers hardness was measured on the rolled surface. The evaluation results are shown in Tables 5 and 6.

[0070] (Bending workability) Samples with a thickness of less than 0.8 mm were bent in accordance with the four test methods in the Japan Copper and Brass Association technical standard JCBA-T307: 2007. Multiple test pieces with a width of 10 mm and a length of 30 mm were taken from the strip material for property evaluation so that the rolling direction and the longitudinal direction of the test piece were parallel and perpendicular to each other, and a W-bend test was performed using a W-shaped jig with a bending angle of 90 degrees and a bending radius that was the same as the thickness of the strip material for property evaluation. Additionally, samples with a thickness of 0.8 mm or more were subjected to bending tests in accordance with the metal material bending test method of Japanese Industrial Standard JIS-Z2248. Multiple test pieces with a width of 20 mm and a length of 30 mm were taken from the strip material for property evaluation so that the rolling direction and the longitudinal direction of the test piece were parallel, and bending tests were performed using the V-block method with a bending angle of 90 degrees and an inner radius of 1.0 mm. The outer periphery of the bent part was then visually inspected and judged as follows: if cracks were observed, it was given a "C", if no cracks were observed but wrinkles were, it was given a "B", and if no breaks or fine cracks were observed, it was given an "A". The evaluation results are shown in Tables 5 and 6.

[0071] (mechanical properties) Test pieces No. 13B specified in JIS Z 2241 were taken from the strip material for property evaluation, and the 0.2% yield strength was measured by the offset method of JIS Z 2241. The test pieces were taken in a direction parallel to the rolling direction. The evaluation results are shown in Tables 5 and 6.

[0072] [Table 1]

[0073] [Table 2]

[0074] [Table 3]

[0075] [Table 4]

[0076] [Table 5]

[0077] [Table 6]

[0078] In Comparative Example 1, the Mg content was lower than the range of the present invention, and therefore the residual stress rate was low, the stress relaxation resistance was insufficient, and the half-softening temperature was low, and the heat resistance was also insufficient. In Comparative Example 2, the Mg content exceeded the range of the present invention, resulting in low electrical conductivity. In Comparative Example 3, the total content of S, P, Se, Te, Sb, Bi, and As exceeded 30 massppm, the residual stress rate was low, and the stress relaxation resistance characteristics were insufficient. In Comparative Example 4, the mass ratio [Mg] / [S+P+Se+Te+Sb+Bi+As] was less than 0.6, the residual stress rate was low, and the stress relaxation resistance characteristics were insufficient. In Comparative Example 5, the average crystal grain size exceeded 100 μm, and bending workability was insufficient. In Comparative Example 6, the average crystal grain size was less than 1 μm, the residual stress rate was low, and the stress relaxation resistance characteristics were insufficient. In Comparative Example 7, the proportion of crystal grains with an aspect ratio b / a of 0.3 or less exceeded 90%, and bending workability was insufficient.

[0079] In contrast, it was confirmed that in Inventive Examples 1 to 24, electrical conductivity and stress relaxation resistance were improved in a well-balanced manner, and bending workability was also sufficiently excellent. From the above, it was confirmed that the present invention can provide a copper alloy having high electrical conductivity, excellent stress relaxation resistance, and excellent bending workability.

Claims

1. The composition has a Mg content in the range of more than 10 ppm by mass and less than 100 ppm by mass, with the balance being Cu and inevitable impurities, and among the inevitable impurities, the S content is 10 ppm by mass or less, the P content is 10 ppm by mass or less, the Se content is 5 ppm by mass or less, the Te content is 5 ppm by mass or less, the Sb content is 5 ppm by mass or less, the Bi content is 5 ppm by mass or less, and the As content is 5 ppm by mass or less, and the total content of S, P, Se, Te, Sb, Bi, and As is 30 ppm by mass or less, When the content of Mg is [Mg] and the total content of S, P, Se, Te, Sb, Bi and As is [S+P+Se+Te+Sb+Bi+As], the mass ratio thereof, [Mg] / [S+P+Se+Te+Sb+Bi+As], is within a range of 0.6 or more and 50 or less, The electrical conductivity is 97% IACS or more. The residual stress rate is 10% or more at 150°C for 1000 hours. The average grain size of the crystal grains is in the range of 1 μm or more and 100 μm or less, For the plane perpendicular to the rolling direction (TD plane), an EBSD measurement device (Quanta FEG 450 manufactured by FEI, OIM Data Collection manufactured by EDAX / TSL (now AMETEK)) and analysis software (OIM Data Analysis Ver. 7.3.1 manufactured by EDAX / TSL (now AMETEK)) were used to analyze the misorientation of each crystal grain (including twins) with an electron beam acceleration voltage of 20 kV, measurement intervals of 0.11 μm, and an area of ​​100,000 μm 2 or more, excluding measurement points with a CI value of 0.1 or less. The measurement points between which the misorientation between adjacent measurement points is 15° or more were defined as grain boundaries, and the grain size on the EBSD was defined as the minimum grain size. A copper alloy characterized in that the proportion of crystal grains having an aspect ratio b / a of 0.3 or less, expressed by the major axis a and the minor axis b of each crystal grain, where the size is 2 pixels, is 90% or less.

2. 2. The copper alloy according to claim 1, characterized in that the Ag content is within the range of 5 ppm by mass to 20 ppm by mass.

3. 3. The copper alloy according to claim 1, wherein the half-softening temperature is 200° C. or higher.

4. A plastically worked copper alloy material comprising the copper alloy according to any one of claims 1 to 3.

5. 5. The plastically worked copper alloy material according to claim 4, which is a rolled plate having a thickness in the range of 0.1 mm to 10 mm.

6. 6. The plastically worked copper alloy material according to claim 4 or 5, characterized in that the surface of the material has a metal plating layer.

7. 7. A part for electronic / electrical equipment, comprising the copper alloy plastically worked material according to claim 4.

8. A terminal comprising the copper alloy plastically worked material according to any one of claims 4 to 6.

9. A bus bar comprising the copper alloy plastically worked material according to any one of claims 4 to 6.

10. A lead frame comprising the copper alloy plastically worked material according to any one of claims 4 to 6.

11. A heat dissipation substrate, which is manufactured using the copper alloy according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Copper rolled sheet and component for electronic and electrical device

    JP2016056414A

  • Superconducting stabilizer, superconducting wire and superconducting coil

    WO2017175711A1